Advancing the Role of Social Mechanisms, Mediators, and Moderators in Securitization Theory: Explaining Security Policy Change in Japan. Issue 3 (2nd September 2019) - Lindgren, Petter Y.
ABSTRACT: In this article, I further develop the Copenhagen School's securitization theory in a causal direction, by emphasizing the explanatory family of mechanisms, mediators and moderators. In the first half of this article, I present two models for conceptualizing the causal maps that securitization is part of. Next, I define five epistemological and methodological dimensions that are important for modelling securitization with causal power. The proposed approach is then put into practice by two most-similar case studies in the second half of the article: securitization attempts in Japan in 2006-07 and in 2012-15. By comparing his securitization efforts in 2006 and in 2012-15 respectively, I identify why PM Abe was successful in his securitization attempt in the latter period. Furthermore, I propose an explanatory set that together with securitization enabled certain effects to take place in Japan, namely the introduction of collective self-defense in 2014/15.